Uma abordagem histórica e metodológica dos métodos de resolução de equação do 2º grau desenvolvidos por Al-Khwarizmi - Santos, Leonardo Silva (2017)
Faced with all problems related to the teaching and learning of Algebra, this work proposes the elaboration and application of a methodological didactic alternative that seeks to give meaning to the teaching and learning process of the methods of resolution of equations of the second degree. Thus, the present work presents the results of the application in a class of 9th year of elementary school of a sequence of activities mediated by the History of Mathematics, which approaches the methods of solving the equation of the second degree developed by Al - Khwarizmi . In order to do so, we sought to investigate the effects of the applied activities, so that the students perceived the construction of the methods while interacting wit h the activities, making the study of this topic more significant. As a methodological approach was used the qualitative research, being characterized as an action type research, with interventions in the classroom. The instruments used for data collection were: questionnaire, sequence of activities in light of the History of Mathematics, observation, logbook, final evaluation and interview. The analysis of the results confirm the objectives of the study, indicating that a methodology based on the development of teaching activities supported in constructivism and mediated by the History of Mathematics provides meaningful learning for the student, since most of the students performed and obtained good results in the applied activities.